Spiritual capital spirituality in practice in Christian perspective - O'Sullivan, Michael; Flanagan, Bernadette (Farnham : Ashgate Publishing Ltd, 2012)
Spiritual Capital seeks to re-focus discussion on core social values, on individuals' value systems and the internal dynamics that impel human beings to live by truth, goodness and love. This book defines, refines and disseminates the concept of spiritual capital. Contributions by practitioner-scholars in applied spirituality, who have practical experience of spiritual capital at work in diverse human situations, provide accounts of concrete expressions of spiritual capital and create an interdisciplinary discussion between spirituality practitioners, artists, ecologists, sociologists and othe.
9Spiritual Capital at Work in the Shadows10Pilgrimage and Spiritual Capital; 11Gardening as a Source of Spiritual Capital; 12Poem-Making, Creativity and Meditative Practice; 13Leonard Cohen, Spiritual Capital and Postmodern Seekers.
Includes index.
Description based upon print version of record.
Keywords: Social Science; SOCIAL SCIENCE / General; Conduct of life; Spirituality; Values; Christian ethics; Christian sociology; Electronic books